DRAMing for autophagy. (20th February 2022) - Leytens, Alexandre; Dengjel, Jörn
Abstract : Autophagy, a catabolic lysosomal recycling pathway, is often found dysregulated in human diseases. Whereas its prime cell stress‐related function is cytoprotection, autophagy has also been linked to the activation of apoptosis and cell death. One group of proteins which participates in the orchestration of autophagy and apoptosis is the family of DRAM proteins. In the current issue of The FEBS Journal, Barthet et al. uncover a compensatory crosstalk between the two newest members of the family, DRAM‐4 and DRAM‐5, the latter one regulating autophagic activity. Comment on https://doi.org/10.1111/febs.16365 Abstract : Autophagy, a catabolic lysosomal recycling pathway, is often found dysregulated in human diseases. One group of proteins which participates in the orchestration of autophagy and apoptosis is the family of DRAM proteins. In the current issue of The FEBS Journal, Barthet et al. uncover a compensatory crosstalk between the two newest members of the family DRAM‐4 and DRAM‐5, the latter one regulating autophagy activity.Comment on: https://doi.org/10.1111/febs.16365